A Critical Review of Biological Processes and Technologies for Landfill Leachate Treatment. Issue 12 (12th November 2015) - Bove, Dario; Merello, Sara; Frumento, Davide; Arni, Saleh Al; Aliakbarian, Bahar; Converti, Attilio
Abstract: The most common method to deal with the huge production of municipal wastes is still the disposal in landfills which, however, generates a leachate with high contents of organic and nitrogen pollutants. Requirements must be fixed by law to control leachate release from such landfills, and effective treatment processes and technologies must be applied to reduce its impact on the environment. Biological processes for leachate treatment are discussed in this review, in the former part of which attention is paid to leachate formation and its qualitative and quantitative features, while the latter deals with the state‐of‐the‐art of the most effective biotechnological treatments presently employed. Processes, alternative methods, and technological improvements are compared, with special focus on novel technologies to remove nitrogen pollutants from leachate, highlighting advantages and drawbacks of each treatment. Abstract : Landfills are built up in a way to avoid waste contact with soil, so they are characterized by a gaseous stream and a liquid one, the so‐called leachate. The main bioprocesses and bioreactors used to treat this pollutant are summarized and compared, highlighting and discussing advantages and drawbacks. Special emphasis is on novel processes for nitrogen removal.